2017
DOI: 10.1186/s13104-017-2957-2
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasitosis and anaemia among patients in a Health Center, North Ethiopia

Abstract: ObjectiveThe aim of this cross-sectional study was to determine the magnitude of intestinal parasitosis and anaemia in a Health Center, North Ethiopia.ResultsA total of 427 outpatients were enrolled and the median age of the participants was 22 years. The prevalence of intestinal parasitosis was 143 (33.5%). Age, place of residence and occupation were significantly associated with intestinal parasitosis. When we see parasite specific factors, significant associations were observed for source of drinking water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
3
14
2
1
Order By: Relevance
“…This was in agreement with the report in Cote d’Ivoire [ 48 ]. This might be an indication for the incomplete separation of human and animal waste with water sources that are used for drinking in the area [ 49 ]. In addition, the resistant cysts of the parasites for routine chlorination might have contributed for the relatively higher infection rates among those who used protected water sources as well.…”
Section: Discussionmentioning
confidence: 99%
“…This was in agreement with the report in Cote d’Ivoire [ 48 ]. This might be an indication for the incomplete separation of human and animal waste with water sources that are used for drinking in the area [ 49 ]. In addition, the resistant cysts of the parasites for routine chlorination might have contributed for the relatively higher infection rates among those who used protected water sources as well.…”
Section: Discussionmentioning
confidence: 99%
“…Even though, all two PTB patients from rural setting in this study were infected with intestinal parasites, it is difficult to compare with urban participants due to bigger numerical differences. However, studies from different parts of Ethiopia showed people who were living in rural areas were at risk of harboring intestinal parasites compared to urban dwellers [11, 12, 31]. Those who had dirty material in their finger nails were about nine times as likely to have intestinal parasites infection compared to those who did not have (AOR = 8.99; 95% CI = 2.46–32.78).…”
Section: Discussionmentioning
confidence: 99%
“…The household was assigned a standardised score for each asset, then the scores were summed for each household to obtain a household wealth index Z -score, which is a continuous measure and the form of the wealth index used in this study. The two environmental factors, average day land surface temperature (LST) and the average enhanced vegetation index (EVI) for 2015, were considered as they serve as proxies for intestinal parasites, which is a risk factor for childhood anaemia [ 20 ]. Moreover, these environmental factors also impact malaria transmission as they affect both the Plasmodium parasite and the host (the Anopheles mosquito).…”
Section: Methodsmentioning
confidence: 99%